On one series of the VI century AD iron one-piece asian helmets - Kubik, Adam L.; Radyuš, Oleg A.; Vyazov, Leonid A. («Քոփի Փրինթ» տպագրատուն)
The article describes a series of helmets of a type that probably spread across Asia and Eastern Europe in the middle to the second half of the VI century AD. These helmets are characterised by a very particular construction: they have a bowl hammered from a single piece of iron, with an additional band in the lower part, connected to the inside or outside edge of the helmet. Additionally, a chainmail collar was attached to the lower part of the helmet. The attached chainmail provides additional protection around the entire circumference including the forehead above the eyes. This characteristic would remain unpopular in European armaments for quite a long period and was only popularised in central and eastern Europe around the XVI century AD [1: 130]. This article analyses a possible Iranian provenance of the helmets of this type as well as hypothesizes about the possible reason for the spread of these helmets on the territory of Eastern Europe and Asia. Հոդվածում նկարագրվում է սաղավարտների մի տեսակ, որը հավանաբար տարածվել է Ասիայում և Արևելյան Եվրոպայում VI դարի կեսերից մինչև դարի երկրորդ կեսը ընկած ժամանակահատվածում: Այդ սաղավարտները բնութագրվում են առանձնահատուկ կառուցվածքով. նրանք պատրաստված են երկաթե մեկ ամբողջական թասանման կտորից, որի ստորին մասում կա լրացուցիչ կապ, որը ամրակցված է սաղավարտի ներսի կամ դրսի եզրին: Բացի այդ, սաղավարտի ստորին մասում ամրացվել է օձիքանման օղազրահ։ Կցված օղազրահը ապահովում է լրացուցիչ պաշտպանություն սաղավարտի ամբողջ շրջագծով մեկ, ներառյալ՝ ճակատամասի: Սաղավարտների այս հատկանիշը բավականին երկար ժամանակ հանրա-ճանաչ չէր եվրոպական սպառազինության մեջ և Կենտրոնական և Արևելյան Եվրոպայում տարածվեց միայն XVI դարում: Հոդվածում քննարկման առարկա է դարձել նաև սաղավարտների այդ տեսակի իրանական ծագման մասին վարկածը, ինչպես նաև առաջ են քաշվում տեսություններ Արևելյան Եվրոպայում և Ասիայում այդ սաղավարտների տարածման հնարավոր պատճառների մասին:
Keywords: History